Assessing the effects of ammonia (NH3) as the secondary fuel on the combustion and emission characteristics with nano-additives. (15th March 2023) - Wu, Yingji; Zhang, Yongnan; Xia, Changlei; Chinnathambi, Arunachalam; Nasif, Omaima; Gavurová, Beata; Sekar, Manigandan; Anderson, A.; Chi, Nguyen Thuy Lan; Pugazhendhi, Arivalagan
Highlights: Ammonia at the two-energy ratio has been tested at wide engine loading conditions. Comparative analysis has been made between the ammonia and nanoparticles role in the combustion and emission. Ammonia blends reported reduced BTE due to poor flame speed. As the concentration increases thermal efficiency dropped significantly with reduced emission of CO. Abstract: Ammonia is a promising alternative to replace the non-renewable fossil fuels. The present work offers the detailed evaluation of ammonia suitability in the diesel engine and how it is affecting the primary properties of the diesel engine. A series of tests was conducted on the test samples such as diesel, B20, B20N, B20A5 and B20A10 across various engine loading conditions. Two different ammonia energy ratios of 5 L/min and 10 L/min have been utilized. In addition to ammonia, the role of nanoparticles was analyzed and compared how far they can be competitive to the green ammonia fuel. 75 ppm of TiO2 nanoparticles was dispersed with  Chlorella vulgaris  microalgae biodiesel blends using ultrasonication. Ammonia was injected as the secondary fuel via air intake. Based on the results, adding ammonia in the diesel engine reduced the brake thermal efficiency of the engine. There was a drastic drop in the brake thermal efficiency that has been reported across various loads. Nevertheless, biodiesel blends with nanoparticles reported peak thermal efficiency due to the enhanced cetane number and calorific value of the fuel. On contrary, the brake specific fuel consumption of B10A and B20A was decreased compared to the other blends. As the ammonia concentration increased, both the peak cylinder pressure and heat release rates were higher. Due to the addition of ammonia, NOx emission was higher due to the higher cylinder temperature. On the other hand, the emissions of carbon dioxide, carbon monoxide and hydrocarbons were reduced for all cases compared to neat diesel.